2013
DOI: 10.1021/ie400790v
|View full text |Cite
|
Sign up to set email alerts
|

Value Added Hydrocarbons from Distilled Tall Oil via Hydrotreating over a Commercial NiMo Catalyst

Abstract: The activity of a commercial NiMo hydrotreating catalyst was investigated to convert distilled tall oil (DTO), a byproduct of the pulp and paper industry, into feedstocks for the production of base chemicals with reduced oxygen content. The experiments were conducted in a fixed bed continuous flow reactor covering a wide temperature range (325−450 °C). Hydrotreating of DTO resulted in the formation of a hydrocarbon fraction consisting of up to ∼50 wt % nC 17 +C 18 paraffins. Comprehensive 2D GC and GC−MS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The reduction of naphthenic acid concentration may be a result of the catalytic decomposition of NAs by molybdenum and/or its corrosion products of molybdenum carbide and molybdenum oxide, as NiMo catalysts are known to reduce organic carboxylic acids at high temperature, and Mo 2 C has been used to decarboxylate organic acids. [21][22][23] The high corrosion resistance of molybdenum is not unexpected, as 316 stainless steel displays improved corrosion resistance in NA vs. 304 stainless steel as a result of the addition of 2.3 wt% Mo, and research has shown that additional molybdenum content further decreases corrosion. 9 In addition, in concentrated fatty acids (∼85%) at high temperatures found in tall oil service (∼275°C), small increases in molybdenum content have a marked effect at decreasing corrosion and pitting of alloys.…”
Section: Molybdenummentioning
confidence: 98%
“…The reduction of naphthenic acid concentration may be a result of the catalytic decomposition of NAs by molybdenum and/or its corrosion products of molybdenum carbide and molybdenum oxide, as NiMo catalysts are known to reduce organic carboxylic acids at high temperature, and Mo 2 C has been used to decarboxylate organic acids. [21][22][23] The high corrosion resistance of molybdenum is not unexpected, as 316 stainless steel displays improved corrosion resistance in NA vs. 304 stainless steel as a result of the addition of 2.3 wt% Mo, and research has shown that additional molybdenum content further decreases corrosion. 9 In addition, in concentrated fatty acids (∼85%) at high temperatures found in tall oil service (∼275°C), small increases in molybdenum content have a marked effect at decreasing corrosion and pitting of alloys.…”
Section: Molybdenummentioning
confidence: 98%
“…Based on these observations, it can be suggested that NiMo catalyst is more applicable than a CoMo catalyst for hydrodeoxygenating bio‐derived oils such as tall oil which contains aliphatic oxygenates as well as cyclic oxygenates. During catalytic hydrotreating of tall oil, oxygenates are removed by various deoxygenation routes which produces a wide range of hydrocarbons mainly paraffin range hydrocarbons .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrotreating of CTO has been discussed in the literature through several patents which mainly focuses the application of hydrotreated products as a diesel fuel . Previously, we successfully reported on the use of hydrotreated DTO and CTO as a steam cracker feed . A high degree of deoxygenation was obtained at low temperatures (325–400°C) and space velocity of weight hourly space velocity (WHSV) = 1 h −1 , yielding a maximum in paraffins.…”
Section: Introductionmentioning
confidence: 99%
“…The lower bound of pressure range corresponds to the processing of easy-to-treat vegetable oils and other plant oils. [16,17] Meanwhile, the upper range is more characteristico fh ydrocracking of heavier oil fractions. Such pressure has also been used in the processing of hydrothermalo ils from lignocellulose or algae.…”
mentioning
confidence: 99%
“…While the density of the product remained slightly outsideroad diesel specifications (0.82-0.845 gcm À3 ), we believe this would be an excellent feedstock for diesel blending, especially for the very paraffinic feedstocks obtained from the hydroprocessing of triglycerides (vegetable oils and others), which tend to have al ow density. [17] Baker et al reported the severe hydroprocessing of ab iocrude,y ieldingafully deoxygenated product with al arge gasoline fraction under the appropriate conditions. [20,21] The biocrude used in the present study had ah igher H/C ratio, lower density and Conradson Carbon Residue, hence improved processability,s ot hat ad iesel range product with low oxygen content could be obtainedu nder less severe hydrotreatingc onditions.…”
mentioning
confidence: 99%